“SIASAT” UKSW (UNIVERSITAS KRISTEN SATYA WACANA) WEBSITE SECURITY ANALYSIS USING OWASP (OPEN WEB APPLICATION SECURITY PROJECT) - Amanda; Indrastanti Ratna Widiasari (Informatika, Universitas Jenderal Soedirman, 2022)
Satya Wacana Christian University (UKSW) is one of the private higher education institutions in Indonesia that utilizes the internet network, namely the web as a medium for conveying information, connecting the academic community and others. UKSW has many webs that are used, one of which is the SIASAT web. SIASAT is Satya Wacana Academic Information System. SIASAT contains important information about the community. Web SIASAT provides information in a private manner or only those with an account can view the information. However, not only people who have access can access the information, but other irresponsible parties can access it in the wrong way and misuse the existing information. So that it can cause harm to the person or organization. SIASAT often experiences security problems with SQL Injection, brute force, and so on but there has never been a hacker who can penetrate the SIASAT web, therefore the SIASAT web needs to be tested for security. Factors that need to be considered in determining security are confidentiality is maintaining the confidentiality of information from unauthorized people, integrity maintaining changes in information from unauthorized people, and availability keeping information accessible. Therefore, in overcoming this problem, one of the steps that can be taken is to analyze the UKSW web where the web to be analyzed is the SIASAT web with the Open Web Application Security Project (OWASP) method. The hope is that with the OWASP, the handling of an attack can be carried out earlier and prevent fatal consequences.